Learning outcomes of occupational therapy and physiotherapy students during their communitybased education attachment - T Ndlovu; T Chikwanha; N Munambah (South African Medical Association, 2017)
Background. Community-based education (CBE) is a learning approach that enables students to acquire skills by means of applied learning in the community. The goals of CBE include creating adequate knowledge, skills and attitudes that facilitate service delivery in communities. These goals ensure the provision of efficient health services to marginalised communities with significant resource constraints. The Department of Rehabilitation at the University of Zimbabwe, Harare, has adopted CBE as one of the learning approaches that enables students to acquire comprehensive skills for future service provision in the community.Objectives. To determine the learning outcomes of rehabilitation students at the University of Zimbabwe and to identify factors affecting learning during the CBE attachments.Methods. A descriptive cross-sectional survey was conducted at the University of Zimbabwe. Thirty-five final-year occupational therapy and physiotherapy students responded to a self-administered questionnaire. Data were analysed using Microsoft Excel 2013 (USA) and SPSS version 21 (IBM Corp., USA).Results. All the students reported that the CBE attachment improved their community-engagement skills, professional skills and personal growth. Barriers to effective learning included inadequate transport (100%), poor internet connectivity (82%), lack of research-related objectives (74%) and inadequate resources for CBE activities (60%).Conclusion. The CBE attachment enabled students to gain skills in community engagement, professionalism and personal growth. However, more funding directed towards CBE activities and introducing objectives related to research, are some of the strategies that might improve the students’ learning outcomes during the attachments.